Tinjauan Filosofis Masalah Aktual Pendidikan Islam ( Pembaruan Pendidikan Pesantren ) - Imam Fakih (Transformasi : Jurnal Studi Agama Islam, 2017)
Pesantren (Islamic Boarding School) is the religious education institute. It is also as model of Islamic Education Institute in Indonesia. Pesantren has a moral responsibility to sharpen nation life, particularly to improve religious life quality for Indonesia moslems. Further develovment stated that pesantren consists of typologies both salafiyah/modern salafiyah, semi salafiyah and integrated islamic boarding school.The writer has own reason to discuss Pesantren Terpadu (Integrated Islamic Boarding School) in which built Madrasah of private university in pesantren terpadu the students or collegians become santri (Islamic Boarding School Student) all at once. An integrated pesantren has own characteristic and all integrities must be done both integrity of vision, mision, integrated program, finance, the equipment nedeed, curriculum, managerial, and teaching technique